Sister Village Collaboration Model: A Comparative Analysis of Village Development Strategies in Economic, Social, and Environmental Sectors in East Lombok and Lebak Regencies, Indonesia - Nurdin, Nurliah; Prasetyanti, Retnayu; Posumah, Riski Yustiani; Hanafi, Sofyan (KnE Social Sciences, 2025)
This study presents a comparative analysis of village development strategies in the economic, social, and environmental sectors in East Lombok Regency, West Nusa Tenggara Province, and Lebak Regency, Banten Province, Indonesia. It uses a mixed-method approach, combining qualitative case studies with quantitative descriptive analysis. Focusing on Grenengan Timur Village in East Lombok and Malabar Village in Lebak, the study examines the disparities in resource accessibility, community participation, and environmental awareness between developing and underdeveloped villages in pursuing sustainable rural development. The findings reveal significant differences in economic access, social support systems, and environmental management practices between the two villages. While Grenengan Timur demonstrates better economic accessibility and stronger social networks, Malabar strives for challenges in infrastructure development and community engagement. Addressing the disparities, the study proposes a “sister village” collaboration model, emphasizing knowledge transfer and best practice sharing between developed and underdeveloped villages. This research contributes to the understanding of rural development dynamics in Indonesia and provides practical recommendations for accelerating progress in underdeveloped villages through inter-village collaboration and targeted interventions in economic, social, and environmental sectors.